CAR-T and TCR-T cellular immunotherapies in oncology - Kobold, Sebastian (Henry Stewart Talks, 2021)
An overview of CAR-T cell therapy, Introduction to the mode of action of CAR-T cell therapy, Differences between CAR-T and TCR-T therapies, Resistance mechanisms to CAR-T cell therapy